2015
DOI: 10.17338/trainology.4.1_6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between isometric mid-thigh pull variables and sprint and change of direction performance in collegiate athletes

Abstract: Objectives:The aim of this investigation was to assess the use of isometric strength testing as a determinant of sprint and change of direction performance in collegiate athletes. Design and Methods: Fourteen male collegiate athletes (mean ± SD; age = 21 ± 2.4 years; height =176 ± 9.0 cm; body mass = 72.8 ± 9.4 kg) participated in the study. Maximal strength was assessed via an isometric mid-thigh pull (IMTP). Isometric mid-thigh pull testing involved trials with peak force (IPF), maximum rate of force develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
130
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 34 publications
11
130
0
1
Order By: Relevance
“…Secondly, to assess the within-session reliability of the unilateral stance IMTP PF measures. It was hypothesized that the relationships between IMTP strength variables and sprint, and CODS would be similar to those previously identified by Thomas et al 21 and Spiteri et al 19 because of the CODS tests used within the studies. It was further hypothesized that unilateral stance IMTP PF measures would demonstrate reliability values similar to those previously identified in the bilateral stance IMTP.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Secondly, to assess the within-session reliability of the unilateral stance IMTP PF measures. It was hypothesized that the relationships between IMTP strength variables and sprint, and CODS would be similar to those previously identified by Thomas et al 21 and Spiteri et al 19 because of the CODS tests used within the studies. It was further hypothesized that unilateral stance IMTP PF measures would demonstrate reliability values similar to those previously identified in the bilateral stance IMTP.…”
Section: Introductionmentioning
confidence: 61%
“…Tillin et al 23 found normalized peak force (PF) at 100 ms during an isometric back squat to correlate to 5-and 20-m sprint performance (r = − 0.54 to − 0.63) in varsity rugby union players. Further, Thomas et al 21 found a significant correlations between IMTP strength and sprint performance (r = − 0.57 to − 0.78) in collegiate athletes. Together, these studies indicate a strong association between maximal strength and sprint performance.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…26 Similarly, the 90˚ cutting task involved sprinting forwards 5 m and performing a 90˚ cut left or right, and exiting 3 m through the finish where timing gates were also placed. If the subject changed direction before hitting the turning line, or changed direction off the incorrect foot, the trial was disregarded and the subject com-pleted another trial after the rest period.…”
Section: Change Of Direction Speed Assessmentsmentioning
confidence: 99%